Media programming : strategies and practices - Eastman, Susan Tyler; Ferguson, Douglas A.; Eastman, Susan Tyler (Belmont, CA : Thomson/Wadsworth, 2006)
This book is primarily about television and radio and it focuses on entertainment and informational programs coming to viewers as pre-produced units of content. -Pref. [This book] provides students with ... information on the techniques and strategies used in the programming industry. [This] text covers all aspects of media programming for broadcast and cable television, radio, and the Internet ... The authors explore how programs (units of content) are selected (or not selected), how programs are arranged in schedules of various kinds, how programs are evaluated by the industry, and how they are promoted to audiences and advertisers. The book also delves into the limits of media programming arising from technology, regulations, policies, and marketing needs, as well as how things like human attention spans, lifestyle patterns and economics determine the availability and arrangement of media entertainment content. -http://www.wadsworth.com.
Rev. ed. of : Broadcast/cable/web programming., 6th ed., 2002
Includes bibliographical references (p. 435-441) and index
Keywords: Television programs -- Planning; Radio programs -- Planning; Cable television -- Planning